Analisis GC-MS Minyak Atsiri dan Uji Antioksidan Kulit Jeruk Manis (Citrus sinensis) Sebagai Lip Balm - Nurmala, Nurmala; Syarifah, Syarifah; Nilsya, Nilsya; Melisa, Melisa; Dina, Dina; Ayu, Ayu; Chairunnisa, Chairunnisa (Journal of Pharmaceutical and Health Research, 2024)
Antioxidants are chemicals that can inhibit or stop other molecules from oxidizing. Antioxidants can be found in the fruit known as sweet orange (Citrus sinensis). Orange peel essential oil is utilized in processed foods, medicines, cosmetics, and aromatherapy in the medical field. Therefore, the objective of this study was to identify the chemical content and antioxidant potential of sweet orange peel to be used as a lip balm. Processing sweet orange peel, steam distillation of essential oil, GC-MS analysis, formulating lip balm preparation, assessing lip balm preparation, and measuring antioxidant activity using a spectrophotometer and DPPH technique, were part of this study. Essential oil from sweet orange peel (Citrus sinensis L.) was analyzed using GC-MS (Gas Chromatography - Mass Spectroscopy), and the results obtained in this study were 1.4 - Cyclohexadiene, 1 - methyl. The lip balm formulation containing essential oil was evaluated as the most preferred formulation. The IC50 value of sweet orange peel essential oil was determined to be 85.2595386 ppm, which converts the antioxidant to strong.